JOURNALISTIC FREEDOM OF EXPRESSION AND CONTEMPT PROCEEDINGS AT THE INTERNATIONAL CRIMINAL TRIBUNAL FOR THE FORMER YUGOSLAVIA - Cubbon, John (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2018)
The International Criminal Tribunal for the former Yugoslavia (ICTY) has addressed the limits to journalistic freedom of expression more frequently and in more detail than other tribunals that resemble it. In its Rules of Procedure and Evidence a broadly common law concept of contempt of the Tribunal was adopted. The jurisprudence of the ICTY establishes that a violation of a court order as such constitutes an interference with its administration of justice and that it is not for a party or a third person to determine when an order “is serving the International Tribunal’s administration of justice”. The Tribunal has also held that the disclosure of confidential evidence by another third party does not mean either that this information is no longer protected or that the relevant court order has been de facto lifted or that its violation will not interfere with the Tribunal’s administration of justice. In deciding whether a restriction of the right of a journalist to freedom of expression was justified, the Appeals Chamber considered whether it was provided by law and whether it was proportionate and necessary for the protection of public order. The jurisprudence of the ICTY in this area is relevant to the practice of other international and internationalized criminal courts because of the similarity of their rules and the comparable impediments to the enforcement of their orders.